Indonesia Country Gender Assessment : Investing in Opportunities for Women - World Bank (World Bank, Washington, DC, 2021)
In 2018, Indonesia’s poverty rate fell below 10 percent for the first time; poverty rates had halved over the previous two decades, driven in large part by strong economic growth in the country. Continued economic growth, rather than changes in distribution, will continue to be a key driver of poverty reduction. The objective of continued economic growth and poverty reduction is apparent in the Government of Indonesia’s new medium-term development plan (Rencana Pembanguanan Jangka Menengah Nasional or RPJMN) (2020-2024). Investments in gender equality to close specific gender gaps have the potential to contribute to greater economic growth for Indonesia, thereby contributing to further poverty reduction. The objectives of this report are to review the current status of gender equality and women’s issues in Indonesia; and to provide an evidence base for the Indonesian Government on specific actions and priority responses needed to close gender gaps to drive the growth and human capital potential of the country. Specifically, the assessment focuses on areas where demonstrated improvements in gender equality can contribute to economic growth, both in the short term through improvements in economic participation, but also over the medium term through investments in human capital. The report starts by providing the assessment framework and context to understand patterns of gender equality in Indonesia in chapter one and chapter two. It then moves to a discussion on women’s economic participation to elucidate the key factors underlying these current trends in chapter three, before moving to a discussion of the current areas Indonesia will need to address to ensure the equivalent human capital accumulation of women across the country in chapter four. It then summarizes some of the early dual health and economic impacts of the novel coronavirus (COVID-19) pandemic in chapter five, before providing a set of strategic priority actions to advance the country’s growth and poverty reduction objectives through investments in gender equality in chapter six.